Cost determination of using bioethanol to improve properties of Nigerian gasoline. (June 2023) - Olugbenga, Adeola Grace
Abstract: Standard octane requirement were targeted with the formulation of an objective function that minimize the cost of blended gasoline using linear program technique. In this method, ASTM gave standard parameter specification. By utilizing the data of the existing refinery which is constrained to produce 15, 000bbl/d, the research octane number (RON) is 93 at 8psi. Based on the refinery input data, the minimized cost of blended and unblended gasoline are 71.65 /bbl and 66.05/bbl respectively. The model allow inputs from bioethanol, FCC gasoline, reformate and light naphtha streams of another refinery. Thus, gasoline properties are altered in procedure including bioethanol addition.